1993
DOI: 10.1111/j.1460-2695.1993.tb00739.x
|View full text |Cite
|
Sign up to set email alerts
|

A Path‐independent Parameter for Fatigue Under Proportional and Non‐proportional Loading

Abstract: A path-independent multiaxial fatigue damage criterion is proposed based on critical plane concepts: fatigue crack growth is controlled by the maximum shear strain, and an important secondary effect is due to the normal strain excursion over one reversal of the maximum shear strain. The effect of loading path on fatigue endurance is quantified by the normal strain excursion. Only one multiaxial material constant is required in the model which can be determined from uniaxial test data plus one torsional result.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
181
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(186 citation statements)
references
References 14 publications
2
181
0
3
Order By: Relevance
“…This paper deals with the comparison of some selected models of fatigue life estimation under stationary non-Gaussian random axial loading on the basis of experimental data obtained for the 10HNAP steel in high cycle fatigue (HCF). In this paper the following models for multiaxial loading are analyzed and their predictions compared with experiments: SmithWatson-Topper damage parameter used by BannantineSocie [5], Fatemi-Socie [5,6], Socie for HCF [7], WangBrown [8,9], Morel [10,11] and Łagoda-Macha [1][2][3][4]. n in spherical coordinates system m s = l 0 variance of a stress history s(t) s a max maximum amplitude in the history of stress after cycle counting by means of the rainf ow algorithm s af fatigue limit in fully reversed tension-compression y angle, from f xed axis in the plane P n →, to def ne the direction where the resolved shear stress is computed…”
Section: Introductionmentioning
confidence: 99%
“…This paper deals with the comparison of some selected models of fatigue life estimation under stationary non-Gaussian random axial loading on the basis of experimental data obtained for the 10HNAP steel in high cycle fatigue (HCF). In this paper the following models for multiaxial loading are analyzed and their predictions compared with experiments: SmithWatson-Topper damage parameter used by BannantineSocie [5], Fatemi-Socie [5,6], Socie for HCF [7], WangBrown [8,9], Morel [10,11] and Łagoda-Macha [1][2][3][4]. n in spherical coordinates system m s = l 0 variance of a stress history s(t) s a max maximum amplitude in the history of stress after cycle counting by means of the rainf ow algorithm s af fatigue limit in fully reversed tension-compression y angle, from f xed axis in the plane P n →, to def ne the direction where the resolved shear stress is computed…”
Section: Introductionmentioning
confidence: 99%
“…Calibrated coefficients from the axial loads are determined using the solid specimen, as the experimental fatigue life for the axial load is determined using a solid specimen [48]. The experimental fatigue life results for titanium alloy BT9 are given in Table 3, and were determined using the tubular specimen Experimental [33] Experimental [48] Fatigue life prediction of titanium alloy for block loading using the hybrid approach of critical plane and continuum damage mechanics [48]. The predicted fatigue, along with the experimental fatigue lives for blocks of loading, are presented in Table 3.…”
Section: Application Of Proposed Modelmentioning
confidence: 99%
“…The accuracy of the proposed model can be further improved by applying the block loading as a full or filtered profile so that only high damage cycles remain and the sequence effect of previous loading cycles can be captured. Experimental [33] Experimental [48] Fatemi Socie Model [48] mainly due to the difference of specimen geometry, as well as the fact that the axial, torsion and out-of-phase profiles are only used for coefficient calibration to estimate the fatigue life for block loads. Generally, the model has shown good accuracy and is simple to apply.…”
Section: Application Of Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The equivalent stress based on von Mises (Mises stress) is generally used in that design for structures under multiaxial loading. In recent literatures of multiaxial fatigue, it is reported that fatigue life evaluated by the Mises stress is overestimated [1][2][3][4][5][6][7][8] and the M magnitude depends on loading path [9][10][11][12][13][14][15][16]. In the multiaxial fatigue under non-proportional loading in which directions of principal stress and strain are changed in a cycle, it has been reported that fatigue lives are reduced accompanying with additional hardening which depends on both loading path and material [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%